(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
Documenting tangible cultural heritage is one of the most significant challenges facing societies, especially in the face of conflict and natural disasters. Archaeological heritage is an essential part of cultural identity, Recording and documenting artifacts using remote sensing is of great importance to preserve it from damage and extinction. Al Azm Palace in Damascus represents one of the most prominent Ottoman architectural landmarks in Syria that goes back to 1749. It contains a collection of heritage and archaeological pieces that reflect traditional Damascene life. Hence, the importance of using modern digital techniques such as photogrammetry to document these artifacts and digitally preserve them for future generations. This research aimed to document a collection of artifacts and heritage items on display at Al-Azm Palace using photogrammetry, a modern digital tool that enables the creation of high-resolution three-dimensional models. Four diverse pieces from the palace’s collection were selected and photographed using a DJI Mavic Air 2 drone, which carries a 1/2" CMOS sensor and 48MP image capture, in addition to a Realme 8 mobile phone quad camera with a resolution of 64-2-8MP. Photogrammetry provided an effective solution for reconstructing 3D models with high accuracy using digital images to create an accurate digital archive. The research showed that the resulting models achieved high geometric accuracy, The similarity rate in geometric proportions reached 98%. reflecting the efficiency of the adopted photogrammetric methodology. The generated models were able to highlight fine details, such as inscriptions and minor deteriorations. Furthermore, DSM models of these artifacts were linked to a GIS, and a dedicated metadata was created for them.